The role of ethnicity in the increased susceptibility to non-alcoholic fatty liver disease in people of Indian origin - Chalmers, Jane (2021)
Introduction Non-alcoholic fatty liver disease (NAFLD) is fast becoming a global health concern. It is closely associated with obesity, diabetes and the metabolic syndrome, has a global pooled prevalence of 25% and is the leading cause of chronic liver disease in Europe and the United States.